The analysis of data quality on topographic maps - Govedarica, Miro (Geodetski vestnik, 2011)
The data quality of topographic maps involves a degree of deviations of geometric and thematic content from their actual position and status in nature, respectively. For determining the geometric accuracy, comparative way of testing is usually applied, namely the comparison of measured values of topographic maps with "true" or "conditionally true" values (numeric data of positional and elevation network or data of a map in a larger scale, where thecontent errors of individual elements could be neglected in comparison due to differences in the scale of mapping). This method gives a direct accuracy assessment of printed maps and reproduction originals, as opposed to the experimental method which considers and determines errors in certain phases inthe process of making topographic maps. Geometric, and to a large extent thematic accuracy of topographic maps are not always reliable enough and depend on the way of surveying and the type of contents, i.e. from geodetic control points, which are more accurate, to vegetation whose positional accuracy is the worst.
Keywords: cartography; classic map; data quality; digital map; digitalna karta; kakovost podatkov; kartografija; klasična karta; topografska karta; topographic map